Closing the gaps in rat cytomegalovirus ALL-03 (Malaysian strain) genomic scaffold - Balakrishnan, Krishnan Nair; Abdullah, Ashwaq Ahmed; Abba, Yusuf; Bala, Jamilu Abubakar; Abdullah, Faez Firdaus Jesse; Mustaffa Kamal, Farina; Allaudin, Zeenathul Nazariah; Ideris, Aini; Mohamed Mustapha, Noordin; Mohd Lila, Mohd Azmi (Science Publications, 2015)
Next generation sequencing technologies has revolutionized genomic research by producing a large volume of sequence data and lowest per base cost compared to the traditional sanger method. Although this technology offers many advantages, gap occurrences are commonly found in draft assemblies. The same problem was observed with RatCytomegalovirus (RCMV) ALL-03 (Malaysia strain), where a complete genome sequence could not produce the complete genome due to the presence of gaps in the draft genome. This restrains our ability to take full advantage of genome data. This study aimed to identify the sequence data present in the gap regions and close these gaps in order to produce a complete genome sequence for RCMV ALL-03. Twenty sets of specific primers were designed between two adjacent contigs and PCR was carried out to obtain the appropriate sequences in respective gap regions. Sanger sequencing was employed in the PCR product to get the gap sequences. Out of the five identified gaps in the RCMV ALL-03 genome sequence, only three were confirmed to be true gaps, while the other two were due to sequence repeats. In conclusion, all the gaps were closed successfully and complete genome sequence of RCMV ALL-03 can now be explored in further studies.